TCP Performance Measurement in GPRS Link Adaptation Process - Al-Khalid, Hj Othman; Muzalina, Zakaria; Khairuddin, Abdul Hamid (Materials and Energy Research Center, 2008)
This paper presents the results of measured TCP performance in the LA process during the deployment of GPRS CS1 and CS2 coding schemes and after the activation of two more coding schemes, CS3 and CS4. The measurements are done under various network scenarios based on users’ physical locations in one of Malaysia’s commercially deployed live GPRS networks. End-to-end FTP file transfer application is used for the assessment together with tracing at the GPRS air interface. The results show that TCP works well in the LA process and can adapt to the frequent switching between the coding schemes without any problem. The average throughput is increased by 23% for urban areas owing to the activation of higher coding schemes and aided by TCP tuning. It is also shown that bad radio condition is the main factor affecting throughput. TCP performance is seen to be constant in all scenarios and it can cope with GPRS mobility and bad radio condition, although at the expense of reduced throughput.